Scanning the Business Environment and Detecting Weak Signals. - Lesca, Humbert (Focus nanoscience and nanotechnology series., 2014)
An increasing number of business executives, managers and political leaders are using the concept of "weak signals" nowadays. There are also an increasing number of people trying to find out exactly what this concept means, as well as when and how to use it. Such questions arise particularly when it comes down to making strategic decisions. To help with these questions, this book defines the concept of the "weak signal" and then demonstrates how it would be useful in relation to strategic decisions, and more precisely in relation to three moments of the strategic decision, i.e.:- The trigger of the strategic decision (what is the trigger, why and when)- The development of the strategic decision- The implementation of the strategic decision.